2012
DOI: 10.1080/09552367.2012.729324
|View full text |Cite
|
Sign up to set email alerts
|

Knowing to Act in the Moment: Examples from Confucius’Analects

Abstract: Many scholars note that the Analects, and Confucian philosophy more generally, hold a conception of knowing that more closely approximates 'knowing-how' than 'knowingthat'. However, I argue that this description is not sufficiently sensitive to the concerns of the early Confucians and their focus on self-cultivation. I propose that a particular conception of knowing-knowing to act in the moment-is better suited to capturing the Analects' emphasis on exemplary lives in actual contexts. These investigations migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Some have suggested that this overall picture of ethical knowledge or expertise cannot be readily assimilated into categories such as 'knowing that' or even 'knowing how'. Instead, some early Ruist texts contain a distinctive notion which we might understand as knowing to, as in knowing to act in the moment (Lai, 2012;Hetherington and Lai, 2015). This too can be understood as a kind of expert skill.…”
Section: Ethical Expertisementioning
confidence: 99%
“…Some have suggested that this overall picture of ethical knowledge or expertise cannot be readily assimilated into categories such as 'knowing that' or even 'knowing how'. Instead, some early Ruist texts contain a distinctive notion which we might understand as knowing to, as in knowing to act in the moment (Lai, 2012;Hetherington and Lai, 2015). This too can be understood as a kind of expert skill.…”
Section: Ethical Expertisementioning
confidence: 99%
“…16 Refer to the helpful discussion of the relation between zhengming and ethics, and whether this passage fits within the ambit of zhengming, in Loy (2014). 17 In earlier work, I suggest that the primary epistemological notion in the Analects is best described as 'knowing to act in the moment' (Lai 2012). 18 Another term in the Analects captures the sense of practice, with emphasis on performance (xi 習: 1.1; 1.4; 17.2).…”
Section: Practicementioning
confidence: 99%